A structural equation modeling study on productivity investments in tourism security of a multi-islands province: Community perspectives for Community-Based Tourism model of Romblon, the Philippines - Avi Ben P. Andalecio; Edwin S. Martin (School of Tourism, Universitas Ciputra Surabaya, 2023)
Sustainable Tourism through Community Development concept developed the niche of Community-Based Tourism (CBT). This niche is seen as having a great impact on rural communities in the Asian Region known for its pro-poor implications that deliver socio-cultural, ecological, political, and economic benefits to communities. This study aims at investigating the potentials of CBT specifically in the multi-island province of Romblon in the Philippines. Using the Extended Theory of Sustainable Development, the researcher attempts to examine the impacts of tourism to shed light on its costs and benefits for the rural communities of Romblon. Analyses on LGUs and Communities through Structural Equation Modeling (SEM) was employed. Results revealed that tourism positively affect the extended parameters of sustainable development. This could be a conclusive basis for a Public Policy Development in the Multi-Island Province.